Pelatihan Public Speaking Sebagai Upaya Meningkatkan Keterampilan Komunikasi dan Ekspresi Siswa dalam Pementasan Drama dan Musikalisasi Puisi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Oral communication skills and artistic expression represent essential competencies that often remain underdeveloped among students, particularly in the context of drama performance and poetry musicalization. This condition is evidenced by students' persistent difficulties in articulating ideas clearly, limited self-confidence when performing before an audience, and an inability to convey expressions appropriate to the roles they portray or the poetic content they present. In response to these challenges, this community service program was designed and implemented through a public speaking training initiative grounded in experiential learning as a strategic intervention. The program was conducted at SMA Negeri 6 Makassar through a systematic sequence encompassing needs assessment, conceptual instruction, technique demonstration, public speaking practice, drama and poetry musicalization simulation, intensive mentoring, and comprehensive evaluation. The results demonstrated measurable improvements in articulatory precision, intonation dynamics, stage command, facial expression and gesture richness, and heightened self-confidence during public performance. High levels of enthusiasm and active engagement further affirmed program effectiveness. These findings underscore that public speaking training integrated with performing arts practice is not only effective as a community service initiative, but also holds substantial potential for adoption as a complementary program within Indonesian Language instruction.